ANALISIS RESEPSI PEREMPUAN MILENIAL PADA FENOMENA CHILDFREE (Studi Pada Blog Gita Savitri Devi Berjudul ''Perempuan yang Diperdebatkan'') - Kintan Dwi Syawalia Janah, (2022)
The existence of the child-free phenomenon in Indonesia currently causing pros and cons in various circles of society. The term childfree is considered taboo and against the norms in Indonesian society. Gita Savitri Devi is one of the female influencers who chose to declare her decision not to want to have children after marriage through her A Cup of Tea Webblog entitled ''Perempuan yang Diperdebatkan''. The content of the webblog raises the picture and point of view of the social stigmas that are still felt to be attached to women in Indonesia. This study aims to find out how the audience, especially millennial women, in interpreting the message conveyed by Gitasav in her webblog. Furthermore, the reception results are categorized into three positions of audience acceptance based on Stuart Hall's encoding-decoding model. This research uses a qualitative descriptive approach with constructivism paradigm and uses reception analysis method. The results obtained through in-depth interviews with 5 informants who have met the criteria indicate that there are 4 informants in the dominant position category and 1 informant in the negotiated position category and no informant in the opposition category.